Isotope discrimination and photosynthesis of vegetation growing in the Bossoleto CO 2 spring - Miglietta, F.; Raschi, A.; Körner, C.; Vaccari, F. P. (Chemosphere, 1998)
The Bossoleto CO2 spring emits CO2 which has a stable carbon isotopic ratio (~5~3C = - 8%o). We determined ~3C on leaves of several individual species growing in Bossoleto and in a nearby control site at ambient CO,.. ~5t3C was 6% more negative in leaves of species collected from the grassland community of Bossoleto, indicating increased discrimination (A) against the heavy carbon isotope. No such changes were found in ruderal species growing in the same spring, suggesting that photosynthetic capacity was much less affected. A was substantially increased under elevated CO2 in leaves of Quercus pubescens but not in Quercus ilex, which also did not show any increase in non-structural carbohydrates. Gas-exchange measurements made on Plantago lanceolata, supported the view that photosynthetic capacity is decreased in plants grown under elevated CO: and on poor soils
Keywords: Elevated CO2; Grassland vegetation (voyant); isotopic discrimination; photosynthetic capacity

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - FARIA, T.; Cerasoli, S.; García-Plazaola, J. I.; Guimaraes, M. P.; Abadia, A.; Raschi, A.; Miglietta, F.; Pereira, J. S.; Chaves, M. M. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M. M.; Pereira, J. S.; Cerasoli, S.; CliftonBrown, J.; Miglietta, F.; Raschi, A.; Chaves J. S. ;Cerasoli, S. ;Clifton Brown (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)The following values have no corresponding Zotero field: pub-location: OSNEY MEAD, OXFORD, OXON, ENGLAND OX2 0EL publisher: BLACKWELL SCIENCE LTD label: Fisiologia - CO2 elevado
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits